PENGKAJIAN KERENTANAN FISIK UNTUK PENGEMBANGAN PESISIR WILAYAH KOTA MAKASSAR - Tejakusuma, Iwan G. (Badan Pengkajian dan Penerapan Teknologi, 2011)
Coastal Vulnerability Index (CVI) was used to analyse the physical vulnerability to coastal disaster of the coastal areas of Makassar City. CVI will consider six variables namely geology, geomorphology, erosion and accretion, tidal range, average wave height and elevation. Geologically, coastal areas of Makassar comprise sand, gravel, clay and coral limestone. Geomorphologically, alluvial plain, sandy to gravelly beaches are predominant in the coastal areas. Both erosion and accretion occurred in the coastal areas in which accretion predominantly found in the southern part whereas erosion in the northern part of the city. Using DigitalElevation Model it can be observed that the elevation of the coastal areas of Makassar City is between 0 – 0.5 meter which is very vulnerable to sea level rise. Average tidal range was between 1.1 to 2 meter and wave height between 0 to 2.9 meter. CVI analyses showed that the coastal areas of Makassar City is vulnerable to sea level rise and hence to the coastal disaster. In addition, according to the analyses, Wajo, Biringkanaya and Tamalanrea districts are very vulnerable to sealevel rise and coastal disaster. Coastal development planning in these veryvulnerable areas will need special attention and specific measures.